212k views
1 vote
Y-5=m(x-6) solve for m

User ZSkycat
by
5.0k points

2 Answers

1 vote

Hi there!

»»————- ★ ————-««

I believe your answer is:


\boxed{m= (y-5)/(x-6)}; \text{ } x\\eq 6

»»————- ★ ————-««

Here’s why:

⸻⸻⸻⸻


\boxed{\text{Solving for 'm'...}}\\\\y-5=m(x-6)\\------------\\\rightarrow m(x-6) = y-5\\\\\rightarrow (m(x-6)=y-5)/((x-6)); x\\eq 6\\\\\rightarrow \boxed{m= (y-5)/(x-6)}; \text{ } x\\eq 6

⸻⸻⸻⸻

»»————- ★ ————-««

Hope this helps you. I apologize if it’s incorrect.

User Jmn
by
5.2k points
4 votes

5 + -6m + mX,

If you like, I can explain a bit more!

User Daniel Sibaja
by
5.2k points